To find the inverse of a function algebraically, we swap the x and y variables and solve for y.
Given the function h(x) = 16x - 5, we can write it as:
x = 16y - 5
Now, let's solve for y:
x + 5 = 16y
y = (x + 5)/16
Therefore, the inverse of h(x) = 16x - 5 is h^(-1)(x) = (x + 5)/16.
Find the inverse of h(x)=16x−5 algebraically.(1 point) Responses h−1(x)=16x+5 h inverse left parenthesis x right parenthesis equals 16 x plus 5 h−1(x)=x16+5 h inverse left parenthesis x right parenthesis equals Start Fraction x over 16 End Fraction plus 5 h−1(x)=x−516 h inverse left parenthesis x right parenthesis equals Start Fraction x minus 5 over 16 End Fraction h−1(x)=x+516
1 answer